Characteristics and factors associated with waiting time for rehabilitation in patients with amputation from a Peruvian referral hospital. - De la Cerna-Luna, Roger (2024)
Objective: To determine the characteristics and factors associated with waiting time for rehabilitation in patients with amputation from the Physical Medicine and Rehabilitation Department of Rebagliati Hospital. Materials and methods: Retrospective cohort with data from medical records between May 2017 and May 2019. Results: A total of 180 patients with amputation were included. 64.4% were 59 years or older, 78.9% were male, and 78.9% were new patients who had not been previously attended. 70.6% had amputation due to vascular causes. 85.6% had lower limb amputation, mostly above the knee. Prolonged waiting time for rehabilitation (three months or more) was more common in new patients or those aged 69 years or older. Conclusions: The majority experienced lower limb amputation, primarily due to vascular or traumatic causes. The median waiting time for rehabilitation was three months, being longer for new patients or those aged 69 and older.